Presentación atípica de nocardiosis pulmonar como pioneumotórax en un paciente en tratamiento con corticoides. - André Fabiano; Anatilde Trindade (Sociedade Galega de Medicina Interna, 2021)
Nocardiosis is a rare opportunistic infection caused by the bacteria Nocardia spp. It may present as a localized infection or as an invasive infection (pulmonary, central nervous system or disseminated). The authors describe a 76-year-old woman under corticotherapy for the last month because of a recent diagnosis of cryptogenic organising pneumonia. She presented to the emergency department with one week evolution of pleuritic chest pain and shortness of breath. Chest radiograph showed a left hydropneumothorax. A chest tube was inserted and the drained pleural effusion was purulent, compatible with a pyopneumothorax. The pleural fluid culture came positive for Nocardia Cyriacigeorgica. Nocardiosis is a serious infection with non-specific presentation making its diagnosis a challenge.